Presence of Listeria monocytogenes and Salmonella spp. in lamb meat commercialized in Uruguaiana, Rio Grande do Sul, Brazil - Mendonça Soares, Vanessa; Nunes da Cruz Encide Sampaio, Aryele; Rodrigues dos Santos, Emanoelli Aparecida; Ereno Tadielo, Leonardo; Gonçalves Pereira, Juliano (Brazilian Journal of Veterinary Medicine, 2021)
The aim of this study was to evaluate the hygienic-sanitary quality of lamb meat sold in the city of Uruguaiana, Rio Grande do Sul (RS) by counting the indicator microorganisms and detecting pathogens such as Salmonella spp. and Listeria monocytogenes. Thirty-nine lamb meat samples were collected from 10 commercial establishments in Uruguaiana. The samples were subjected to counts of aerobic mesophilic microorganisms and enterobacteria, and to the detection of Salmonella spp. and L. monocytogenes, all following standard methods. The average counts of mesophilic microorganisms and enterobacteria were 6.08 log CFU/g (minimum 4.07 and max 6.87) and 4.73 log CFU/g (minimum 0 and max 5.88), respectively. For pathogens, L. monocytogenes was isolated from five samples (12.82%), with three samples in the same location. Only two samples (5.13%) were positive for Salmonella spp. The results demonstrated unsatisfactory hygienic-sanitary conditions because high counts of pathogens such as Salmonella spp. and L. monocytogenes. The counts of enterobacteria showed poor hygiene conditions during the various stages of production. The results also indicated fecal contamination, as Salmonella spp. and L. monocytogenes are present in the intestinal tract of both humans and animals. The high count of mesophilic microorganisms obtained could be owing to contaminated raw material or unsatisfactory processing, including unsanitary conditions and the inappropriate use of binomial time/temperature during storage.